2018
DOI: 10.5539/jas.v11n1p430
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Fertilization and Rhizobacteria in the Control of Meloidogyne javanica in Common Bean Plants

Abstract: The effects of treating seeds of the common bean with rhizobacteria before sowing associated with different nitrogen (N) doses on the control of the nematode Meloidogyne javanica was evaluated. The assay was carried out in a greenhouse in random blocks, with a factorial arrangement of 5 × 5 + 1: five N doses (0, 25, 50, 100, and 200 kg/ha); five isolates: Bacillus pumilus (1, 60 and 76), Bacillus subtilis.-34, Bacillus sp.-36, and one control treatment. The plants were inoculated with 3,000 nematode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Longer and fine roots, for the same mass (same metabolic consumption), present a larger surface area and, consequently, in a higher capacity to absorb nutrients, mainly those with low mobility in the soil, such as phosphorus. The rhizobacterium evaluated in the present study (B. subtilis-34) has been shown to be efficient in promoting the growth of vegetable, common bean, and banana plants (Lopes et al, 2019a;Lopes et al, 2019b;Santos et al, 2019;Lopes et al, 2018). Most studies found in the literature evaluated rhizobacteria and water-retaining materials separately (Basyony and Abo-Zaid, 2018;Andrade et al, 2023), thus neglecting the potential synergistic effects of the combined use of these agents.…”
Section: Discussionmentioning
confidence: 95%
“…Longer and fine roots, for the same mass (same metabolic consumption), present a larger surface area and, consequently, in a higher capacity to absorb nutrients, mainly those with low mobility in the soil, such as phosphorus. The rhizobacterium evaluated in the present study (B. subtilis-34) has been shown to be efficient in promoting the growth of vegetable, common bean, and banana plants (Lopes et al, 2019a;Lopes et al, 2019b;Santos et al, 2019;Lopes et al, 2018). Most studies found in the literature evaluated rhizobacteria and water-retaining materials separately (Basyony and Abo-Zaid, 2018;Andrade et al, 2023), thus neglecting the potential synergistic effects of the combined use of these agents.…”
Section: Discussionmentioning
confidence: 95%